Tongkonan Transformation: Function, Form, and Material in Toraja Church - Brian Riyona Bayurangga Kadam; Agus Dwi Hariyanto (Advances in Civil Engineering and Sustainable Architecture, 2025)
This study explores the transformation of function, form, and materials in the adaptation of the traditional Tongkonan house into the Toraja Church in Surabaya. The Tongkonan, a culturally significant dwelling for the Toraja's people, undergoes various changes when adapted to an urban context. Using a qualitative descriptive method and comparative analysis, this research examines differences between original Tongkonan houses and their architectural reinterpretation in the Surabaya church. The findings reveal that the function has shifted from residential to religious use, materials have changed from wood, bamboo, and thatch to concrete, steel, and glass, while the iconic curved roof form has been largely retained. These changes reflect a balance between preserving cultural identity and meeting modern building requirements. The study highlights how vernacular architecture can evolve through adaptation, offering a sustainable approach that respects tradition while responding to contemporary needs in urban environments.